Colorectal carcinoma presenting in the orbit: mass effect from an uncommon cause. (4th July 2021) - Long, Christopher P.; Lu, Tianlun; Ediriwickrema, Lilangi S.; Lin, Jonathan H.; Korn, Bobby S.; Kikkawa, Don O.; Liu, Catherine Y.
ABSTRACT: An 84-year-old male with previously documented poor medical follow-up presented with progressive painless proptosis of the right eye. Right upper eyelid ptosis, limited motility, proptosis, and inferomedial displacement of the right globe were noted on the exam. Computed tomography (CT) imaging revealed a right retrobulbar extraconal heterogenous mass with ill-defined borders. Biopsy revealed a malignant adenocarcinoma with tumor markers suggestive of a colorectal primary. A rectal mass was identified during a systemic workup. After biopsy, the patient was diagnosed with stage IV metastatic rectal adenocarcinoma. He began palliative radiation therapy shortly following diagnosis.